Diagnostic performance of the visual caries classification of International Caries Detection and Assessment System II versus conventional radiography for the detection of occlusal carious lesions in primary molars - Jayachandra Reddy Bhumireddy; S V. S. G. Nirmala; Sreekanth Kumar Mallineni; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim of the present study was to evaluate the accuracy in the diagnosis of the occlusal caries lesion using the International Caries Detection and Assessment System II (ICDAS II) and conventional bitewing radiographs in primary molars. Materials and Methods: A total of 35 children was selected randomly and recruited for visual ICDAS II and conventional bitewing radiographic examination by two independent trained examiners. Two hundred and fifty-four teeth were examined at D1 (enamel caries lesions) and D3 (dentine caries lesions) thresholds. Results: Sensitivity and specificity at D1 for ICDAS II was 100%, whereas it was 2.97% and 100%, respectively, for bitewing radiographs. At D3 threshold, sensitivity and specificity of ICDAS II was 94.55% and 96.45%, whereas it was 60.0% and 98.99% respectively for bitewing radiographs. Conclusion: ICDAS II is better than conventional bitewing radiographs in detecting carious lesions that confined to enamel, and both are equally effective in the detection of dentinal carious lesions.